1996
DOI: 10.1021/ja962026p
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Triggered Secondary Structure Changes in the Aggregated States of a Designed Methionine-Rich Peptide

Abstract: We have previously shown that methionine can be used as a “switchable” residue for the design of peptides with alternative secondary structure preferences in the aggregated state (J. Am. Chem. Soc. 1993, 115, 12609). Redox-induced secondary structure changes in the 18-residue peptide Ac-YLKAMLEAMAKLMAKLMA-NH2 result from conversion of lipophilic methionine (M) to hydrophilic methionine sulfoxide (M°), which transforms a peptide capable of adopting an amphiphilic α-helical conformation into a peptide capable of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 40 publications
4
61
0
1
Order By: Relevance
“…These results are qualitatively in good agreement with experiments which show that polyalanine adopts an α-helical conformation in hydrophobic environments such as the solid state or in non-polar organic solutions and a β-structure conformation in polar aqueous solution 88,[106][107][108][109][110][111] . This is similarly observed in experiments on many heterogeneous peptides which can be folded into alternative stable structures by changing the solution conditions such as the pH, salt or organic cosolvent concentration, peptide concentration, and the redox state [112][113][114][115][116][117][118][119][120][121][122][123][124][125][126] . Interestingly, Knott and Chan 95 recently investigated the impact of the relative strengths of the hydrophobic and hydrogen bonding interaction on folding of polypeptide chains using a similar intermediate-resolution protein model 94 but with a continuous potential.…”
Section: Resultsmentioning
confidence: 80%
“…These results are qualitatively in good agreement with experiments which show that polyalanine adopts an α-helical conformation in hydrophobic environments such as the solid state or in non-polar organic solutions and a β-structure conformation in polar aqueous solution 88,[106][107][108][109][110][111] . This is similarly observed in experiments on many heterogeneous peptides which can be folded into alternative stable structures by changing the solution conditions such as the pH, salt or organic cosolvent concentration, peptide concentration, and the redox state [112][113][114][115][116][117][118][119][120][121][122][123][124][125][126] . Interestingly, Knott and Chan 95 recently investigated the impact of the relative strengths of the hydrophobic and hydrogen bonding interaction on folding of polypeptide chains using a similar intermediate-resolution protein model 94 but with a continuous potential.…”
Section: Resultsmentioning
confidence: 80%
“…that show that polyalanine adopts an ␣-helical conformation in hydrophobic environments such as the solid state or in nonpolar organic solutions and a ␤-structure conformation in polar aqueous solution (Ingwall et al 1968;Platzer et al 1972;Shoji et al 1990;Blondell et al 1997;Kimura et al 1998;Lee and Ramamoorthy 1999;Warrass et al 2000). This is also observed in experiments on many heterogeneous peptides that can be folded into alternative stable structures by changing the solution conditions such as the pH, salt, or organic cosolvent concentration; peptide concentration; and the redox state (Rosenheck and Doty 1961;Kabsch and Sander 1984;Mutter and Hersperger 1990;Mutter et al 1991;Reed and Kinzel 1991;Zhong and Johnson 1992;Cohen et al 1993;Dado and Gellman 1993;Waterhous and Johnson 1994;Cerpa et al 1996;Fukushima 1996;Schenck et al 1996;Zhang and Rich 1997;Tuchscherer et al 1999;Awasthi et al 2001;Wildman et al 2002). Although there are many computer simulation studies in which the transition between ␣-helix and random coil of polyalanines is observed (Okamoto and Hansmann 1995;Vila et al 1998;Hansmann and Okamoto 1999;Alves and Hansmann 2000;Mitsutake and Okamoto 2000;Alves and Hansmann 2001;Garcia and Sanbonmatsu 2002;Olivella et al 2002;Peng and Hansmann 2002;Ghosh et al 2003;Ohkubo and Brooks III 2003;…”
Section: Discussionmentioning
confidence: 79%
“…For example, many peptides are well known to undergo a sharp helix-coil transition as the temperature is increased (Poland and Scheraga 1970;Rohl and Baldwin 1998). Furthermore, the conformational transition between the ␣-helix and ␤-structure is greatly influenced by solvent conditions, including the pH (Mutter and Hersperger 1990;Cerpa et al 1996;Tuchscherer et al 1999), the temperature (Cerpa et al 1996;Fukushima 1996;Zhang and Rich 1997), the salt or organic cosolvent concentration (Mutter and Hersperger 1990;Mutter et al 1991;Reed and Kinzel 1991;Cerpa et al 1996;Zhang and Rich 1997;Awasthi et al 2001), the peptide concentration (Cerpa et al 1996), and the redox state (Dado and Gellman 1993;Schenck et al 1996). Despite the important role played by the solvent conditions in the ␣-␤ transition, our understanding of these effects is far from complete.…”
Section: Introductionmentioning
confidence: 99%
“…Nle has a methylene group substituted for the sulfur atom in the side chain~Fig. 1!, and it is more hydrophobic than Met Schenck et al, 1996!. It has been shown in a number of reports that both Eth and Nle can be readily incorporated into proteins in place of Met residues~Yoshida & Yamasaki, 1959;Trupin et al, 1966;Anfinsen & Corley, 1969;Kerwar & Weissbach, 1970;Brown, 1973;Old & Jones, 1976;Alix et al, 1979;Barker & Bruton, 1979;Gilles et al, 1988;Koide et al, 1988;Bogosian et al, 1989;Randhawa et al, 1994;Thomson et al, 1994!.…”
mentioning
confidence: 99%